Cold-induced biochemical changes in leaves of two commercial clones of Eucalyptus - Basile, Patricia; Wallace, Federico; Olivaro, Cristina; De Palma, Nicolás; Borsani, Omar; Fett-Neto, Arthur (Frontiers in Molecular Biosciences, 2025)
IntroductionCold weather poses a significant challenge to the growth of crops and subtropical tree species like Eucalyptus. Exposure of plants to stressful temperatures generates changes in their physiology resulting from modifications in gene expression and extensive metabolic reorganization. A direct comparison of several biochemical changes under cold exposure of leaf tissues of E. dunnii and E. grandis clones was carried out.MethodsLeaf discs of E. grandis and E. dunnii were initially maintained for 24 h at 25°C and then 4 days at 6°C to induce cold stress. Sampling was conducted at 0 h (control condition), 2 and 4 days. Several biochemical parameters were measured, and an untargeted metabolomics approach based on ultra-high performance liquid chromatography (UHPLC) coupled to linear ion trap mass spectrometry fingerprinting was carried out.ResultsResults indicated distinct cold tolerance strategies in Eucalyptus grandis and Eucalyptus dunnii. Eucalyptus dunnii initiated protective mechanism activation after a 2-day exposure period with the accumulation of sugars and phenolic compounds, whereas E. grandis did so after 4 days, accumulating proline and anthocyanins. PLS-DA based on UHPLC-MS fingerprints revealed a clear species-specific effect across the metabolome. This effect was greater than the differences between cold temperatures. Additionally, this methodology allowed the putative identification of 16 phenolic marker compounds with high discriminant potential to differentiate the cold response in these two species.